Analysis of fractional COVID-19 epidemic model under Caputo operator - Zarin, Rahat; Khan, Amir; Yusuf, Abdullahi; Abdel-Khalek, Sayed; İnç, Mustafa (Wiley, 2023)
The article deals with the analysis of the fractional COVID-19 epidemic model (FCEM) with a convex incidence rate. Keeping in view the fading memory and crossover behavior found in many biological phenomena, we study the coronavirus disease by using the noninteger Caputo derivative (CD). Under the Caputo operator (CO), existence and uniqueness for the solutions of the FCEM have been analyzed using fixed point theorems. We study all the basic properties and results including local and global stability. We show the global stability of disease-free equilibrium using the method of Castillo-Chavez, while for disease endemic, we use the method of geometrical approach. Sensitivity analysis is carried out to highlight the most sensitive parameters corresponding to basic reproduction number. Simulations are performed via first-order convergent numerical technique to determine how changes in parameters affect the dynamical behavior of the system.
Keywords: epidemic model; numerical simulations; sensitivity analysis; stability analysis